CO2 em zeólita LTA obtida de argila pinheiro do Estado de Sergipe - Ramos, Victor Hugo dos Santos (2019)
This study aimed to synthetize the LTA zeolite using Pinheiro clay state of Sergipe (LTA-PIN), currently limited clay for the production of ceramic artifacts, for CO2 adsorption in static system. The Pinheiro clay was treated with HCl for the removal of organic matter and metals. The LTAPIN zeolite was synthesized by two-step route using calcination followed by hydrothermal treatment. The characterization was performed using the techniques of XRD, XRF, SEM, TG/DTA and FT-IR. The main crystalline phases identified in Pinheiro clay were muscovite, ilite, calcite, montmorillonite and quartz. The crystalline restructuring of the clay was evidenced by XRD and the synthesis of LTA zeolite was verified by comparison with the crystallographic cards being obtained with 95.70% of purity. The CO2 adsorption experiments on LTA zeolite were performed using the static volumetric method performed at 25°C, for 1 h, by varying the initial CO2 pressure between 0.05-0.36 MPa using 2 g of adsorbent. The kinetic study showed that the adsorption of CO2 in the pores of the LTA-PIN zeolite occurs in the first 30 min and is best represented by the pseudo second order kinetic model with Qe of 101.26 mg g-1 and k2 of 0.0014 g mg-1 min-1 . The LTA-PIN zeolite presented adsorption capacity of 131.44 mg g-1 with chemical equilibrium described by the Langmuir isotherm indicating chemical adsorption and presenting high regenerative capacity.